Supporting Data for The Cycladic Blueschist Unit on Tinos, Greece: Cold NE Subduction and SW-Directed Extrusion of the Cycladic Continental Margin under the Tsiknias Ophiolite - Lamont, TN; Palin, RM; Searle, MP; Gopon, P; Roberts, NMW; Wade, J; Waters, DJ (University of Oxford, 2020)
Data collected during Tom Lamont DPhil.